DEVELOPMENT THE EFFECTIVENESS OF WHATSAPP AS ONLINE LEARNING MEDIA INCLASS IV SD 101871 SIDODADI - Rabiatul Adawiyah; Umar Darwis (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2021)
This study aims to determine the effectiveness of Whatsapp as an online learning media in the fourth grade of SD 101871 Sidodadi. The number of samples is 28 students in the fourth grade of SD 101871 Sidodadi. The data analysis technique that the author uses in this study is a qualitative method. The data collection used is by using interview sheets, questionnaires, stationery / recording equipment. The results of the research discussion state that the effectiveness of whatsapp as an online learning medium during the pandemic helps teachers in the learning process. The application that is presented is very friendly, practical and not much choice of rules what to do when operating it. Obstacles that occur while using whatsapp media during online learning, when students do not have an internet connection or internet package., Students do not have sufficient funds to buy internet packages so that teaching and learning activities stop and children do not get teaching that day, Signals in one village The problem was interrupted so that students could not receive messages from the teacher for these activities, finally we the teacher had to pick up the student's house, the student only had a communication device or 1 cellphone and it was used for more than one person at the house, so our experience when seeing In this condition, the child always takes turns with his brother or sister or brother in using the cellphone. Sometimes his parents also use the HP. Signals in one village The problem was interrupted so that students could not receive messages from the teacher for these activities, finally we the teacher had to pick up the student's house, the student only had a communication device or 1 cellphone and it was used for more than one person at the house, so our experience when seeing In this condition, the child always takes turns with his brother or sister or brother in using the cellphone. Sometimes his parents also use the HP. Signals in one village The problem was interrupted so that students could not receive messages from the teacher for these activities, finally we the teacher had to pick up the student's house, the student only had a communication device or 1 cellphone and it was used for more than one person at the house, so our experience when seeing In this condition, the child always takes turns with his brother or sister or brother in using the cellphone. Sometimes his parents also use the HP. Keywords:WhatsApp and Learning Media.